2017
DOI: 10.1002/dev.21523
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of salivary sample collection in an international pediatric cohort: The the TEDDY study

Abstract: Saliva offers a relatively noninvasive method for measuring analytes such as cortisol, holding particular promise for use in pediatric populations on a large scale if a rigorous collection protocol is feasible in diverse settings. The Environmental Determinants of Diabetes in the Young study protocol, conducted in centers in the US, Sweden, Finland and Germany, used salivary collection to assess cortisol level as a physiologic marker of stress. Saliva was collected using Sorbettes from subjects at 3.5, 4.5, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Other studies of home salivary collection in adults have shown similar results, with good compliance and high rates of acceptability (36,37) and studies in children have reported levels of compliance above 90% in participants as young as 3.5 years (38,39). There are limitations of our studies.…”
Section: Stability Of Salivary Cortisol Collected By Salivette and Pa...supporting
confidence: 49%
“…Other studies of home salivary collection in adults have shown similar results, with good compliance and high rates of acceptability (36,37) and studies in children have reported levels of compliance above 90% in participants as young as 3.5 years (38,39). There are limitations of our studies.…”
Section: Stability Of Salivary Cortisol Collected By Salivette and Pa...supporting
confidence: 49%
“…The issues that complicate the reliability of the sample, such as eating, drinking, and exercise, would not be a concern for our population, and saliva collection devices for children and infants are now commercially available. 23 A limitation was that ours was a single-center study with a relatively small sample size. More than half of the infants transported during our study period were excluded from the study; however, excluded infants were noted to be of similar clinical acuity as those included.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is especially important in longitudinal research, since an uncomfortable or difficult sample collection method could contribute to drop-out of study participants. The use of saliva sample collection at home to assess salivary hormones has been studied before, and was considered feasible and acceptable by both parents and children aged between 3.5 and 5 [25] and over 9.5 years old [26]. In these studies, feasibility was based on whether the samples contained sufficient material to perform analysis and whether samples were collected on the required time points.…”
Section: Discussionmentioning
confidence: 99%